Untersuchungen über die hämocytären Reaktionen der Insektenhämolymphe gegen Bacillus thuringiensis Berliner-Infektionen am Beispiel des Kiefernspanners Bupalus piniarius Linnaeus (Lepidoptera: Geometridae). - Adam, Heinz (Contributions to Entomology = Beiträge zur Entomologie, 1970)
These studies furnish information about the effects of Bacillus thuringiensis Berliner on caterpillars of the pine moth Bupalus piniarius Linnaeus. The course of the infection was observed by blood counts. It was established that the changes in the haemolymph which occur with an infection by Bacillus thuringiensis are typical and can be classified.